Untargeted Metabolomics of Nicotiana tabacum Grown in United States and India Characterizes the Association of Plant Metabolomes With Natural Climate and Geography - Ma, Dong-Ming; Gandra, Saiprasad V. S.; Manoharlal, Raman; La Hovary, Christophe; Xie, De-Yu (Frontiers in Plant Science, 2019)
Climate change and geography affect all the living organisms. To date, the effects of climate and geographical factors on plant metabolome largely remain open for worldwide and local investigations. In this study, we designed field experiments with tobacco (Nicotiana tabacum) in India versus USA and used untargeted metabolomics to understand the association of two weather factors and two different continental locations with tobacco metabolism. Field research stations in North Carolina, USA and Rajahmundry, India were selected to grow a commercial tobacco genotype (K326) for two years. Plant growth, field management, and leaf curing followed protocols standardized for tobacco cultivation. GC-MS based unbiased profiling annotated 171 non-polar and 225 polar metabolites from cured tobacco leaves. Principal component analysis (PCA) and hierarchical cluster analysis (HCA) showed that two growing years and two field locations played primary and secondary roles affecting metabolite profiles, respectively. PCA and Pearson analysis, which used nicotine, 11 other groups of metabolites, two locations, temperatures, and precipitation, revealed that in North Carolina, temperature changes were positively associated with the profiles of sesquiterpenes, diterpenes, and triterpenes, but negatively associated with the profiles of nicotine, organic acids of TCA, and sugars; in addition, precipitation was positively associated with the profiles of triterpenes. In India, temperature was positively associated with the profiles of benzenes and polycyclic aromatic hydrocarbons, but negatively associated with the profiles of amino acids and sugar. Further comparative analysis revealed that nicotine levels were affected by weather conditions, nevertheless, its trend in leaves was by plants themselves. All these findings suggested that climate and geographical variation significantly differentiated the tobacco metabolism.